Solid-liquid interdiffusion (SLID) bonding in the Au–In system: experimental study and 1D modelling. (3rd November 2015) - Deillon, Léa; Hessler-Wyser, Aïcha; Hessler, Thierry; Rappaz, Michel
Abstract: Au–In bonds with a nominal composition of about 60 at.% In were fabricated for use in wafer-level packaging of MEMS. The microstructure of the bonds was studied by scanning electron microscopy. The bond hermeticity was then assessed using oxidation of Cu thin discs predeposited within the sealed packages. The three intermetallic compounds AuIn2, AuIn and Au7 In3 were observed. Their thickness evolution during bonding and after subsequent heat treatment was successfully modelled using a finite difference model of diffusion, thermodynamic data and diffusion coefficients calibrated from isothermal diffusion couples. 17% of the packages were hermetic and, although the origin of the leaks could not be clearly identified, it appeared that hermeticity was correlated with the unevenness of the metallisation and/or wafer and the fact that the bonds shrink due to density differences as the relative fractions of the various phases gradually evolve.